Antidiabetic Activity of Lactobacillus fermentum Bacteria from Dengke Naniura Goldfish (Cyprinuscarpio) in Nicotinamide-Streptozotosin Induced Rats - H, Syahputri; J, Silalahi; U, Harahap; D, Satria (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: This study aims to determine the effect of Lactobacillus fermentum on decreasing blood glucose levels, sRAGE, HbA1c levels.Methods: Testing was done on male rats, which consisted of 7 groups. Group 1 as negative control was given Na-CMC0.5%, group 2 was given Lactobacillus fermentum isolate dose 0.5mL, group 3 was given Lactobacillus fermentum isolate dose 1mL, group 4 was given Lactobacillus fermentum isolate dose 1.5mL, group 5 was given Lactobacillus fermentum isolate dose 2 mL, group 6 as positive control was given glibenclamide dose 0.45 mg/kg, and group 7 as the normal group. Decreased KGD, sRAGE, HbA1C.Results: The results of statistical analysis showed that the administration of Lactobacillus fermentum showed the effect of a decrease in blood glucose (KGD) rats that were not significantly different than the positive control group (p <0.05). From the results of testing the Lactobacillus fermentum 2 mL treatment group gave the best results on decreasing sRAGE levels; decreased HbA1C.Conclusion: Based on the results of this study Lactobacillus fermentum bacteria can reduce blood glucose, sRAGE, HbA1C levels in rats induced by Nicotinamide-Streptozotosin.